On the Origin of Orphan Tremors and Intraplate Seismicity in Western Africa - Olugboji, T.; Shirzaei, Manoochehr; Lu, Yingping; Adepelumi, A. A.; Kolawole, F. (Frontiers in Earth Science, 2021)
On September 5–7, 2018, a series of tremors were reported in Nigeria’s capital city, Abuja. These events followed a growing list of tremors felt in the stable intraplate region, where earthquakes are not expected. Here, we review available seismological, geological, and geodetic data that may shed light on the origin of these tremors. First, we investigate the seismic records for parent location of the orphan tremors using a technique suitable when a single-seismic station is available such as the Western Africa region, which has a sparse seismic network. We find no evidence of the reported tremors within the seismic record of Western Africa. Next, we consider the possibility of a local amplification of earthquakes from regional tectonics, reactivation of local basement fractures by far-field tectonic stresses, post-rift crustal relaxation, landward continuation of oceanic fracture zones, or induced earthquakes triggered by groundwater extraction. Our assessments pose important implications for understanding Western Africa’s intraplate seismicity and its potential connection to tectonic inheritance, active regional tectonics, and anthropogenic stress perturbation.